"Let your hair down" A. V. H. Hartendorp the man and his works - Canseco, Anicia G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1974)
This paper contains a listing of the works of Abram Van Heyningen Hartendorp, published and unpublished, selected on the basis of their research value as Filipiniana materials. This includes books, articles, correspondence, essays, poems, and editorials, the latter, forming the greater bulk of this paper. It seeks to focus the significant contributions of Hartendorp in the fields of Philippine history, education, science, literature, culture (arts and music), politics and government, and economics.
Each entry is annotated, giving a complete bibliographic information of its source. As a background on the study of this paper, and to give an insight into the character of Hartendorp, his interest and love for the country and its people, a biographical sketch of the man is given.
This paper is intended to serve as a valuable source of information for scholars and researchers on many phases of Philippine life, history, and culture.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Hartendorp, Abram Van Heymingen